Alginate-Chitosan Coated Nanoliposomes as Effective Delivery Systems for Bamboo Leaf Flavonoids: Characterization, In Vitro Release, Skin Permeation and Anti-Senescence Activity - Yanpei Gu; Zhenlei Zhao; Fan Xue; Ying Zhang (MDPI AG, 2022)
The use of bamboo leaf flavonoids (BLF) as functional food and cosmetic ingredients is limited by low bioavailability and difficulty in being absorbed by the intestine or skin. The aim of this study was to prepare BLF-loaded alginate-chitosan coated nanoliposomes (AL-CH-BLF-Lip) to overcome these challenges. The nanocarriers were characterized by dynamic light scattering, high performance liquid chromatography, Fourier transform infrared spectroscopy and differential scanning calorimetry. The biological activity was analyzed by in vitro antioxidant activity, transdermal absorption, cytotoxicity and AAPH induced HaCaT cell senescence model. The results showed that the size of nanocarriers ranged from 152.13 to 228.90 nm and had a low polydispersity index (0.25-0.36). Chitosan (CH) and alginate (AL) were successfully coated on BLF-loaded nanoliposomes (BLF-Lip), the encapsulation efficiency of BLF-Lip, BLF-loaded chitosan coated nanoliposomes (CH-BLF-Lip) and AL-CH-BLF-Lip were 71.31%, 78.77% and 82.74%, respectively. In addition, BLF-Lip, CH-BLF-Lip and AL-CH-BLF-Lip showed better in vitro release and free radical scavenging ability compared with naked BLF. In particular, the skin permeability of BLF-Lip, CH-BLF-Lip, and AL-CH-BLF-Lip increased 2.1, 2.4 and 2.9 times after 24 h, respectively. Furthermore, the use of nanoliposomes could significantly improve the anti-senescence activity of BLF (p < 0.01). Conclusively, alginate-chitosan coated nanoliposomes are promising delivery systems for BLF that can be used in functional foods and cosmetics.